Pharmacological Evaluation Of Some Medicinal Plants For Hypoglycemic Activity - Chavan, Sarika; Rajurkar, V G.; Patwekar, Varsha; B. Rakhunde, Purushottam (Journal of Neonatal Surgery, 2025)
Diabetes mellitus is a long-term metabolic disorder marked by ongoing hyperglycemia and related issues, such as dyslipidaemia and oxidative stress. The current study sought to assess the antidiabetic and antioxidant properties of specific medicinal plants—Glycyrrhiza glabra, Pterocarpus marsupium, Syzygium aromaticum, and Aegle marmelos—both individually and as a polyherbal formulation. We used DPPH, ABTS radical scavenging assays, and total antioxidant capacity to test the antioxidant activities in vitro. Syzygium aromaticum exhibited the highest antioxidant activity among individual extracts, whereas the polyherbal formulation displayed increased efficacy, indicating a synergistic effect. To test the polyherbal formulation in living animals, Wistar rats with diabetes caused by streptozotocin were given doses of 200 mg/kg and 400 mg/kg for 30 days. We kept an eye on the levels of blood glucose, triglycerides, and VLDL. The polyherbal extract caused blood glucose levels to go down in a dose-dependent and statistically significant way, with the 400 mg/kg group showing the strongest effect. Moreover, triglyceride and VLDL levels enhanced in the treated groups, suggesting hypolipidemic potential. The polyherbal formulation was not as strong as the standard antidiabetic drug (glibenclamide), but it worked well every time. These results indicate that the polyherbal formulation, abundant in bioactive phytochemicals such as flavonoids, tannins, and alkaloids, may serve as a promising candidate for the management of diabetes and its complications. More research is needed to find the active ingredients and test their long-term safety and effectiveness.